EXPLOIRING CUSTOMER RELATIONSHIP MANAGEMENT AND CUSTOMER’S VALUE ON CUSTOMER’S LOYALTY OF GO-JEK ONLINE SERVICES - Santi Wiji Astuti; Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this research is to understand the influence of Customer Relationship Management (CRM) and customer’s value on costumer’s loyalty of Go-Jek online service users in Samarinda. The sample is concluded by purposive sampling technique, with 140 respondents. Data collection technique used is quesionare (inquiry). Analysis technique used in this research is multiple linear regression analysis by using SPSS 26 progam. The result of the study prove that customer relationship management has a positive and insignificant effect on customer’s loyalty, while the customer’s value has a positive and significant on customer’s loyalty.